A highly efficient 4-terminal perovskite/silicon tandem solar cells using QIBC and IBC configurations in the top and bottom cells, respectively. (August 2022) - Abbasiyan, Amin; Noori, Mina; Baghban, Hamed
Abstract: For obtaining high power conversion efficiency in a 4-terminal perovskite/silicon tandem solar cell, the quasi-interdigitated back contact has been implemented in the top cell, which serves as the grating to improve the photocurrent generation and enhances the fill factor due to the reduction of series resistance. The optical and electrical characteristics of the back contacts in the top and bottom cells have been investigated, and an intermediate quasi-periodic structure of FC(3, 3) has been used to fulfill the power management between the top and bottom cells. Optimized parameters for the proposed back contacts for the perovskite and Si cells are (P = 750 nm, W/P = 0.4) and (Gap = 50 μm, Wn /Wp  = 0.2), respectively. The study has been carried out by the finite element method, and the electrical simulation supports nonideality factors such as recombination in layers and interfaces to provide reliable results in practice. Finally, a reasonable power conversion efficiency of 29.65% has been achieved for the optimized structure with MAPbI3 top (20.3%) and Si bottom (9.35%) cells. Because of the rapid optical and electrical advancement in the field of material analysis for perovskites, here, the simulation steps present a valuable road map to design 4-terminal perovskite/silicon tandem solar cells, in general. Graphical abstract: Image 1 Highlights: A 4-terminal perovskite/Si tandem solar cell has been presented. Quasi-interdigitated and interdigitated back contacts are implemented. A high power conversion efficiency of 29.65% has been achieved.